Respostas

2014-04-20T10:25:12-03:00
2 x^{2} -4x+ log_{2} a=0

x^{2} -2x+  \frac{ log_{2} a}{2}=0

x^{2} -2x+  \frac{1}{2} .log_{2} a}=0

x^{2} -2x+  log_{2}  a^{ \frac{1}{2} } }=0

x^{2} -2x+  log_{2}   \sqrt{a}  } }=0

Δ ≥ 0

Δ = b^{2} -4.a.c ⇒ não é o mesmo a da equação acima!

b^{2} -4.a.c0

(-2)^{2} -4.1.( log_{2} \sqrt{a})0

4 -4 log_{2} \sqrt{a}0

1 -log_{2} \sqrt{a}0

 log_{2} \sqrt{a} ≤ 1

É uma inequação logarítmica.

a > 0

\sqrt{a} 2^{1}

 (\sqrt{a})^{2}2^{2}

a4

Associando as duas condições:

0 < a4
1 5 1